2016
DOI: 10.3389/fimmu.2016.00335
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Including Exosomes Regulate Innate Immune Responses to Hepatitis B Virus Infection

Abstract: The innate immune system is essential for controlling viral infection. Hepatitis B virus (HBV) persistently infects human hepatocytes and causes hepatocellular carcinoma. However, the innate immune response to HBV infection in vivo remains unclear. Using a tree shrew animal model, we showed that HBV infection induced hepatic interferon (IFN)-γ expression during early infection. Our in vitro study demonstrated that hepatic NK cells produced IFN-γ in response to HBV only in the presence of hepatic F4/80+ cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
143
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(147 citation statements)
references
References 46 publications
2
143
0
1
Order By: Relevance
“…As discussed in this review, toxic Aβ peptides and toxic species of P-Tau, neuroinflammation, and oxidative stress can all alter exosome content, secretion rate, and the cell-to-cell messages they carry. Several reports indicate that exosomes produced under pathological conditions can either confer protection or increased pathology to their target cells (Borland and Vilhardt 2017; Chiarini et al 2017; Goetzl et al 2016; Goetzl et al 2017; Kapogiannis et al 2015; Kouwaki et al 2016; Lee et al 2016; Li et al 2013; Papandreou and Tavernarakis 2017). Further study of these processes will provide new insights into how AD pathology spreads throughout the brain and the role of exosomes in this process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in this review, toxic Aβ peptides and toxic species of P-Tau, neuroinflammation, and oxidative stress can all alter exosome content, secretion rate, and the cell-to-cell messages they carry. Several reports indicate that exosomes produced under pathological conditions can either confer protection or increased pathology to their target cells (Borland and Vilhardt 2017; Chiarini et al 2017; Goetzl et al 2016; Goetzl et al 2017; Kapogiannis et al 2015; Kouwaki et al 2016; Lee et al 2016; Li et al 2013; Papandreou and Tavernarakis 2017). Further study of these processes will provide new insights into how AD pathology spreads throughout the brain and the role of exosomes in this process.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this study revealed that treatment with IFN-α changes the cargo content of mRNAs and miRNA in exosomes, which were presumed to be primary communicative agents on antiviral activity via alterations in gene expression. Another study revealed that exosomes modulated IFN-γ-induced innate immune responses to viral infection in vivo (Kouwaki et al 2016). IFN-γ modulation of immune response may involve dendritic cells (DCs), which control T-cell–mediated immune responses and modulate adaptive immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…HBV is a hepadnavirus and is a major cause of hepatocellular carcinoma. Recently, we found that EVs released from HBV-infected hepatocytes contain viral RNA, which is transferred to macrophages [36], resulting in the expression of NKG2D ligands, such as ULBP1 and ULBP2. The expression of NKG2D ligands in macrophages is known to induce NK cell-mediated IFN-γ production [46,47], and we observed that intravenous infection with HBV induced hepatic IFN-γ expression in an animal model [36].…”
Section: Extracellular Vesicles Released From Virus-infected Cellsmentioning
confidence: 99%
“…Chisari and colleagues first reported that exosomes released from HCV-infected hepatocytes carry viral RNA and deliver it to plasmacytoid DCs (pDCs) and stimulate TLR7, which results in the production of type I IFN [35] (Figure 1C). Later, we found that conventional DCs (cDCs) and macrophages sense the viral RNAs within EVs released from HCV or hepatitis B virus (HBV)-infected hepatocytes and evoke antivirus innate immune responses via TLRs and RLRs [36,37] (Figure 1C). In this review, we summarize recent findings related to the role of host and viral RNAs within EVs in the antiviral innate immune response [36,37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation